2003
DOI: 10.1590/s1516-89132003000400021
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in Sargassum Biomass, Hypnea epiphytism and associated fauna

Abstract: Studies were carried out to investigate the temporal variation in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
2
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 30 publications
5
44
2
13
Order By: Relevance
“…Studies have shown that algal biomass may be a measure of its complexity, since higher values of biomass may be related to increased living space, food availability and protection from predators, favoring epiphytic species richness and abundance (HECK & WETSTONE 1977, STONER 1980, LEITE & TURRA 2003. Despite this, in this study S. cymosum biomass was not related to hydroid species richness.…”
Section: Discussioncontrasting
confidence: 55%
“…Studies have shown that algal biomass may be a measure of its complexity, since higher values of biomass may be related to increased living space, food availability and protection from predators, favoring epiphytic species richness and abundance (HECK & WETSTONE 1977, STONER 1980, LEITE & TURRA 2003. Despite this, in this study S. cymosum biomass was not related to hydroid species richness.…”
Section: Discussioncontrasting
confidence: 55%
“…Sessile epibiont organisms such as hydrozoans, sponges and particularly epiphytic algae influence the abundance and diversity of phytal fauna (Kangas, 1978;Leite & Turra, 2003), because they increase the complexity of the macrophytes on which they develop (Bell et al, 1984;Hall & Bell, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…This structural variation can determine differences in the composition and relative abundance of epiphytic algae and of the associated epifauna (Jacobucci et al, 2009). Among the organisms of the macro-epifauna whose occurrence can be influenced by the presence of epiphytes in Sargassum fronds, there are various species of amphipods (Norton & Benson, 1983;Martin-Smith, 1993;Viejo, 1999;Leite & Turra, 2003), some of which utilize algae not only as refuge, but also as a food resource. This is the case with gammarid amphipods of the families Ampithoidae and Hyalidae, for which there are reports of the utilization of epiphytes and Sargassum (Zimmerman et al, 1979;Duffy, 1990;Duffy & Hay, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This only record was thought to be due to its occasional presence associated with seasonality and abundance of Sargassum sp. The density of Hippolyte obliquimanus is higher in autumn-winter periods in association with these algae , which also influence variations in abundance of many caridean shrimp species (Leite and Turra 2003). The decrease in abundance of Sargassum sp.…”
Section: Discussionmentioning
confidence: 99%